The influence of brand image, price, foreign branding, brand ambassador, family, and peer group on repurchase decisions in the fashion industry - Firmansah, Hafiz Gusti; Jatmiko, Jatmiko (Nur Science Institute, 2024)
The industrial sector has heightened competitiveness as the economy progresses, especially among companies producing similar products. These conditions require companies to adapt to changes in both the social and cultural landscape. This study aims to determine the impact of brand image, price, foreign branding, brand ambassadors, family, and peers on repurchase decisions and to identify which variables wield the most influence among brand image, price, foreign branding, and brand ambassadors. Sampling was conducted using non-probability methods employing purposive sampling techniques, yielding 245 respondents who purchased Geoff Max products at least twice a year. Based on the test, the brand image positively affected repurchase decisions, while price exhibited a negative effect. Similarly, foreign branding showed a negative effect, whereas brand ambassadors, family, and peers all displayed positive effects on repurchase decisions. Other test results show that brand image, price, foreign branding, brand ambassador, family, and peer group collectively positively affect repurchase decisions.